Differential insecticide resistance in Bemisia tabaci (Hemiptera: Aleyrodidae) field populations in the Punjab Province of Pakistan. Issue 12 (December 2022) - Saleem, Muhammad; Hussain, Dilbar; Hasan, Mansoor ul; Sagheer, Muhammad; Ghouse, Ghulam; Zubair, Muhammad; Brown, J.K.; Cheema, Sikander Ali
Abstract: The cotton whitefly Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae) has a propensity for developing high-level resistance to insecticides. Management of B. tabaci in cotton grown in Pakistan depends on insecticide use, resistance monitoring has become essential to minimize the development of resistance. In this study, resistance was monitored in adult whiteflies collected from cotton fields in the Bahawalpur, Faisalabad, Lodhran, Multan, and Vehari districts of the Punjab Province, Pakistan during 2017, 2018, and 2019. Resistance monitoring was carried out for two insect growth regulators (pyriproxyfen and buprofezin) four neonicotinoids acetamiprid, imidacloprid, thiamethoxam, thiacloprid, and the historically used pyrethroid, bifenthrin and organophosphate, chlorpyrifos. Results based on resistance ratio (RR) showed that moderate to high level of resistance against noenicitinoids insecticides have been observed in all four districts while whiteflies exhibited very low to low resistance to pyriproxyfen and buprofezin. The RRs for acetamiprid, imidacloprid, thiamethoxam, thiacloprid varied from 7.60 to 50.99, 19.32 to 65.72, 17.18 to 54.65 and 6.49–47.49-fold, respectively. Bifenthrin and chlorpyrifos showed very low toxicity against whiteflies in all districts except Faisalabad, with RRs of 12.28–50.56-fold and 7.94–26.24-fold, respectively. The results will facilitate 'smart' selection and guide rates of insecticide applications for whitefly management in cotton for effective whitefly management while also delaying the development of resistance. Abstract : Insecticide resistance; Insect growth regulators; Neonicotinoids; Whitefly.